Fine-Scale Community Structure Analysis of ANME in Nyegga Sediments with High and Low Methane Flux - Roalkvam, Irene; Dahle, Håkon; Chen, Yifeng; Jørgensen, Steffen L.; Haflidason, Haflidi; Steen, Ida H. (Frontiers in Microbiology, 2012)
To obtain knowledge on how regional variations in methane seepage rates influence the stratification, abundance and diversity of anaerobic methanotrophs (ANME) we analyzed the vertical microbial stratification in a gravity core from a methane micro-seeping area at Nyegga by using 454-pyrosequencing of 16S rRNA gene tagged amplicons and quantitative PCR. The results were compared with previously obtained data from the more active G11 pockmark, characterized by higher methane flux. A downcore stratification and high relative abundance of ANME was observed in both cores, with transition from an ANME-2a/b dominated community in low-sulfide and low-methane horizons to ANME-1 dominance in horizons near the sulfate methane transition zone (SMTZ). The stratification was over a wider spatial region and at greater depth in the core with lower methane flux, and the total 16S rRNA copy numbers were two orders of magnitude lower than in the sediments at G11 pockmark. A fine-scale view into the ANME communities at each location was achieved through OTU clustering of ANME-affiliated sequences. The majority of ANME-1 sequences from both sampling sites clustered within one OTU, while ANME-2a/b sequences were represented in unique OTUs. We suggest that free living ANME-1 is the most abundant taxon in Nyegga cold seeps, and also the main consumer of methane. The specific ANME-2a/b ecotypes could reflect adaptations to the geochemical composition at each location, with different affinities to methane. Given that the ANME-2a/b population could be sustained in less active seepage areas, this subgroup could be potential seed populations in newly developed methane-enriched environments.